Skin vascularisation field by the ascending branch of the peroneal artery ramus perforans - Gačević Milomir; Milisavljević Milan; Novaković Marijan; Vojvodić Danilo; Milosavljević Ivica; Jović Milena; Đorđević Boban; Borović Žarko; Ostojić Nikola; Lalković Mikica; Milićević Saša (Vojnosanitetski Pregled)
Background/Aim. Soft tissue defects in the distal third of the lower leg are persistent and constitute a major problem in the reconstructive surgery. This study presents an analysis of the anatomical vascularization filed of ascending branch of the peroneal artery ramus perforans (PARS). The aim of this study was to assess reliability of the distal flap on the antero-lateral aspect of a lower leg distal third. Methods. Direct gentiana violet injection into the interosseal perforator of ten fresh cadaveric lower legs with subsequent corrosion acrylic preparation was performed to reveal vascularization filed of the ascending branch of the PARP. Height, length, diameter and communication of perforating branch and its subsequent smaller ascending and descending branches were determined. The CAMIA software was used. Results. Our results show that the PARP is always present. Its origin from the peroneal artery is at the medial height of 66 mm when measured from the inferior border of the lateral malleolus. Medium length of ramus perforans is 51.7mm. After transition through the interosseous membrane, ramus perforans divides into ascending and descending branches. The diameter proximal to the level of bifurcation is 1.37 mm (variation 1.0-1.8 mm), and the diameter of the ascending branch distal to the level of bifurcation is 1 mm. Using CAMIA software, the medium length, width and area of the vascularization filed labeled with gentian violet were calculated to be 164 mm (variation 125-210 mm), 66 mm (57-77 mm), and 10,305 mm2 (6,385 mm2-14,341 mm2), respectively. Conclusion. Our results support the use of fasciocutaneous distal flap, vascularized by the ascending branch of the PARP for reconstruction of soft tissue defects in the distal third of the lower limb, malleolar regions and dorsum.